Resistência ao ataque de cupins em painéis compensados confeccionados com paricá (Schizolobium amazonicum (HUBER) DUCKE) - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The difficulty in the process of obtaining solid wood for making furniture and structures became increasingly using products from reconstituted wood as pellets, plywoods, MDF, MDP and OSB. On one hand, there is a better use of the wood, but otherwise the binder used in its manufacture does not prevent the product to resist to the attack of termites and wood-destroying organisms such as fungi. These organisms degrade cellulosic derived products causing economic damages, reducing its quality over time. These organisms, termites cause damage at higher speed and in large proportions. To avoid constant replacement panels because these agents, it is necessary to know which adhesive used provides greater resistance to this product. So objective is to test the resistance of plywoods made of Schizolobium amazonicum (paricá) and different adhesives action of subterranean termite Nasutitermes corniger two methodologies food preference performed in water tanks. In test 1, moisture corrected with sand was used as substrate, while in test 2, there was no type of substrate. In these trials, the colonies was placed near the test samples, made up of panels with urea-formaldehyde (UF), phenol-formaldehyde (FF) adhesive, witnesses and solid wood. All samples had blocked its side to prevent the attack in cross sections and the results was obtained from the weight loss, strength classification and evaluation of wear, ASTM D 2017 specifications. The results indicate that, for the 1 test all panels were classified as nonresistant, but distinguished from the others for less mass loss, FF with 72.64% and UF with 81.624% for the second test, the FF-based panel obtained 33.911% in weight loss and has been classified as moderately resistant. Thus, it was concluded that the panels FF offset base are more resistant to termites than UF-based panels, and among the tests adopted, the test method was one which provided further damage.
Keywords: Paricá (Schizolobium amazonicum); Cupins; Compensados; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL